(untitled) (ACME, 2016)
Although the female characters in Julius Caesar are given little stage time and are ill-treated by their husbands, this article shows that it is not a misogynous play, but a play which effectively depicts a misogynous world. On the one hand, it validates the standpoint of the characters marked as feminine and therefore irrational. On the other hand, the silencing of the feminine poetic and prophetic voice is one of the mainsprings of the tragedy since it is the main characters’ inability to heed this voice which brings about their downfall.